Inflammatory Status of Excavated Pulp Tissue and Internal Root Resorption in Pulpotomized Primary Molars - Roula Berbari; Nahla Nassif; Elia Sfeir (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Internal root resorption after pulpotomy is a pathological phenomenon and can lead to early root resorption and subsequent loss of the tooth.Purpose: To assess the relationship between initial inflammatory coronal pulp status in decayed primary molars treated by pulpotomy and internal root resorption after one-year follow-up.Materials and Method: In this clinical in vivo and in vitro experiment, vital pulpotomies were performed on 50 primary molars from 50 patients aged 5 to 10 years. Coronal pulp was carefully removed followed by hemostasis and placement of a reinforced zinc oxide eugenol over the vital radicular pulp. Enzyme-linked immunosorbent assay (ELISA) assay was done on coronal pulp samples and the level of tumor necrosis factor-alpha (TNF- α) and interlukin-6 (IL-6) was measured. After a 12-month follow-up, periapical radiographs were taken from pulpotomized teeth. Kolmogorov-Smirnov, Chi-square, Kruskal-Wallis, and Mann-Whitney tests were implemented.Results: 11 treated teeth (22%) showed an internal root resorption as diagnosed on X-rays. No significant association was found between TNF- α, IL-6 levels, and pathological root resorption respectively (p= 0.953) and (p= 0.944). A significant association between age and pathological root resorption was observed (p= 0.031). No significant association between remaining dentin thickness and pathological root resorption was established (p= 0.346).Conclusion: There was no association between pro-inflammatory cytokines levels/ TNF- α, IL-6 and internal root resorption following pulpotomy in pediatric patients.